Penerapan Prinsip Mengenal Pengguna Jasa Serta Kepastian Hukum terhadap Akta Pendirian Perseroan Terbatas oleh Notaris yang Berafiliasi dengan Biro Jasa - Natalia, Krisma; Ma'mun, Elma Meliana Eka Putri (Universitas Batanghari Jambi, 2025)
Apart from having the authority to make authentic deeds, notaries also have the authority to identify users of their services. The authority of a Notary to apply the principle of recognizing service users is the attribution authority obtained from Permenkumham No. 9 of 2017 and the legal consequences for a Notary who does not apply this principle is that the Notary may be subject to administrative sanctions based on UUJN. In applying the principle of recognizing service users, Notaries are asked to dig up information in the form of the identity of service users and the acquisition of sources of funds which will later be reported to PPATK. In order to approach writing, the author uses a normative juridical research approach. The writing in this research emphasizes the legal norms contained in in legislation and court decisions as well as legal norms inherent in society.